1995
DOI: 10.1007/bf02790109
|View full text |Cite
|
Sign up to set email alerts
|

Lipoperoxides as an index of free radical activity in bone marrow transplant recipients

Abstract: It has been previously demonstrated that the conditioning therapy given to bone marrow transplant (BMT) recipients creates a high oxidant stress, resulting in a measured reduction in antioxidants, such as glutathione peroxidase (GSH-Px), vitamin E, and cell peroxide fragilities. As part of a current intervention trial of antioxidant therapy in BMT recipients, plasma thiobarbituric acid reactive substances (TBARS) were measured to assess peroxidation and free radical activity. Measurements were performed before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
30
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 31 publications
5
30
0
Order By: Relevance
“…However, several studies showed that antioxidants do not interfere with and can actually enhance the killing capabilities of cancer therapeutic modalities and decrease their side effects. [3][4][5][6][7] Conditioning therapy preceding HSCT usually consists of high-dose chemotherapy. A limited number of studies has shown that high-dose chemotherapy decreased antioxidant enzyme and vitamin levels in patients undergoing HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several studies showed that antioxidants do not interfere with and can actually enhance the killing capabilities of cancer therapeutic modalities and decrease their side effects. [3][4][5][6][7] Conditioning therapy preceding HSCT usually consists of high-dose chemotherapy. A limited number of studies has shown that high-dose chemotherapy decreased antioxidant enzyme and vitamin levels in patients undergoing HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…They have severe acute and delayed toxic effects on several tissues, such as mucous membranes, gastrointestinal tract, liver, lung, bladder, central nervous system, and, rarely, other tissues possibly related to peroxidation processes and exhaustion of antioxidants. [3][4][5][6][7] It is well known that chemotherapy and radiation therapy are associated with the formation of reactive oxygen species and depletion of antioxidants, such as glutathione (GSH), antioxidant enzymes, and antioxidant vitamins such as a-tocopherol, b-carotene and vitamin C. 4,[8][9][10][11] A limited number of studies demonstrated that the conditioning therapy given to HSCT patients creates a high oxidative stress, resulting in a measured reduction in antioxidants. In summary, these studies revealed a disturbance of the pro-oxidative/antioxidative balance in the plasma of patients undergoing HSCT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that BMT was not successful in patients with high plasma TBA-RS concentrations following irradiation. 12 The findings suggest that the prevention of lipid peroxidation at sites other than the BM is important for successful transplantation. Przybyszewski et al 30 reported that the TBA-RS concentration in serum and heart increased about 4 days after fractionated gammairradiation, and the increase was diminished by vitamin E treatment.…”
Section: Discussionmentioning
confidence: 98%
“…In their study, they evaluated lipid peroxidation by the thiobarbituric acid (TBA) method which has been criticized for its lack of specificity. 9,10 Although the concentrations of antioxidants in plasma have been reported to decrease following TBI in humans, 5,11,12 changes in the concentrations of antioxidants and the association of these changes with lipid peroxidation have not been clarified, particularly in the BM. Accordingly, it is of interest to determine how lipid peroxidation occurs in the BM following irradiation, and whether lipid peroxidation is influenced by antioxidant treatment.…”
mentioning
confidence: 99%